ChemInform Abstract: Efficient and Highly Enantioselective Construction of Trifluoromethylated Quaternary Stereogenic Centers via High‐Pressure Mediated Organocatalytic Conjugate Addition of Nitromethane to β, β‐Disubstituted Enones. Issue 17 (April 2015) - Kwiatkowski, Piotr; Cholewiak, Agnieszka; Kasztelan, Adrian
Abstract In comparison to previously developed methods, this high pressure procedure offers several advantages such as a much broader substrate scope, a lower loading of commercially available catalysts, shorter reaction times, and higher enantioselectivities.